Convolutional Neural Network for Predicting COVID-19 from Chest x-ray Images - Albariqi, Anwar Ali A. (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2022)
The world has recently witnessed many deaths for all age groups due to the respiratory COVID-19 but detecting this disease in its early stages helps to recover, avoid negative effects, and reduce the outbreak of the disease quickly. Many symptoms of this disease were found, most notably chest infections and shortness of breath resulting from infection with this disease. The goal of this project is to use chest x-rays images to predict whether a person has the COVID-19 or not. In this study, we tested the solution performances for our problem on different versions of the CNN. Such as Mobile Net, CNN with Adam optimizer, CNN with Data Augmentation, CNN with Batch Normalization, CNN with Leaky Relu, CNN with Dropout, CNN with Early Stopping, CNN with Hyper-parameter Tuning, RESNET50, VGG-16, and VGG-19. The results showed that the VGG-19 model outperformed all the models in detecting infection with MERS-Cove quickly and with high accuracy instead of regular examinations that take a long time and thus limit the spread of the disease.

ÖZ: Dünya son zamanlarda solunum yolu kaynaklı COVID-19 nedeniyle tüm yaş grupları için birçok ölüme tanık oldu, ancak bu hastalığın erken evrelerinde tespit edilmesi iyileşmeye, olumsuz etkilerden kaçınmaya ve hastalığın salgınının hızla azalmasına yardımcı oluyor. Bu hastalığın birçok semptomu bulundu, özellikle de göğüs enfeksiyonları ve bu hastalığa bağlı enfeksiyondan kaynaklanan nefes darlığı. Bu projenin amacı, bir kişinin COVID-19'a sahip olup olmadığını tahmin etmek için göğüs röntgeni görüntülerini kullanmaktır. Bu çalışmada, problemimizin çözüm performanslarını CNN'nin farklı versiyonları üzerinde test ettik. MobileNet, Adam optimizer ile CNN, Veri Artırma ile CNN, Toplu Normalleştirme ile CNN, LeakyRelu ile CNN, Bırakma ile CNN, Early Stopping ile CNN, Hiperparametre Ayarlama ile CNN, RESNET-50, VGG-16 ve VGG-19. Sonuçlar, VGG-19 modelinin, uzun zaman alan ve böylece hastalığın yayılmasını sınırlayan düzenli muayeneler yerine MERS-Cove ile enfeksiyonu hızlı ve yüksek doğrulukla tespit etmede tüm modellerden daha iyi performans gösterdiğini gösterdi.
Master of Science in Computer Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2022. Supervisor: Assist. Prof. Dr. Ahmet Ünveren.
Keywords: Computer Engineering Department; Computational intelligence--Deep Learning; Computer assisted--Image processing; Identification--Data processing; COVID-19, deep learning, VGG-19, conventional neural network, chest x-rays